PENYULUHAN DI DESA KEDUNGGEMPOL KABUPATEN MOJOKERTO “CERDAS TENSI” CEGAH DAN KENDALIKAN HIPERTENSI - Ananda Rigi Aditya; Ayu Cahyani Noviana; Wike Herawaty; Gegel Purnomo Wicaksono; Mochammad Mirza Arif Pranata; Deby Rahmayanti; Dordya Paquita Wijaya; Zahrah Aswa Ananta; Sella Dela Hanna Putri Aziz; Christin Merlina Wattimury; Alya Rosyidah Putri Ramadhani; Nur Khamidah (Jurnal Riset Multidisiplin Edukasi, 2026)
Hypertension is a non-communicable disease with a high prevalence in Indonesia (34.1%) and poses a risk of serious complications such as stroke, heart failure, and chronic kidney disease, thus requiring promotive and preventive efforts through health education. The “CERDAS TENSI” (Prevent and Control Hypertension) health education program was conducted on February 11, 2026, in Kedunggempol Village, Mojokerto Regency, targeting 25 elderly participants enrolled in the Prolanis program within the Modopuro Primary Health Center working area. The activities included a pre-test, interactive education on hypertension and healthy lifestyle practices, a question-and-answer session, a post-test, blood pressure and random blood glucose screening, as well as medical consultation. The evaluation results showed an increase in knowledge completeness from 64% to 80% (a 16% improvement), indicating that the program was effective in enhancing elderly participants’ understanding of hypertension prevention and control and encouraging the adoption of healthy lifestyle behaviors to reduce the risk of complications.